PENGARUH MANAJEMEN SARANA DAN PRASARANA TERHADAP PENINGKATAN KUALITAS PEMBELAJARAN DI MAN 1 KOTA TASIKMALAYA - Yeni Rahmawati; Rahmatul Fajri, Laili; Doni Nugraha (Program Studi Manajemen Pendidikan Islam, 2024)
This research aims to describe the influence of facilities and infrastructure management on improving the quality of learning at MAN 1 Tasikmalaya City. This research uses a quantitative approach with descriptive methods. Research data collection was carried out through distributing questionnaires. The informants in this research were teachers, head of madrasah, head of library, and head of facilities and infrastructure at MAN 1 Tasikmalaya City. Data analysis was carried out using quantitative analysis techniques which included data collection,data testing, data presentation, and drawing conclusions. Meanwhile, to check the validity of the data, researchers used validity and reliability tests with the IBM SPSS Statistics 26.0 MacOS application. The results of this research indicate that the level of tendency for management of facilities and infrastructure and the quality of learning at MAN 1 Tasikmalaya City is in the medium category. In the determination test that was carried out, the calculation result was 29.8%, this figure means that the classroom management variable has an influence on learning motivation, while 70.2% is another factor that was not studied. Then the influence of facilities and infrastructure management on improving the quality of learning at MAN 1 South Tangerang City, based on the results of statistical testing (T-test). With the test criteria if the significance value is < α (0.05) then there is an influence. The results of the T-Test carried out obtained a significance value of 0.000, where it can be seen that 0.000 < 0.005 means that there is a significant influence between the management of facilities and infrastructure on improving the quality of learning at MAN 1 Tasikmalaya City.